Defining and measuring housing affordability using the Minimum Income Standard. Issue 8 (14th September 2019) - Padley, Matt; Marshall, Lydia; Valadez-Martinez, Laura
Abstract: There is growing concern about a crisis in housing affordability in the UK, renewing longstanding debates about what constitutes 'affordable' housing. The growing use of the private rented sector by low income households has also led to increased interest in understanding the impact of housing costs on living standards. This paper builds on existing work on 'residual income' measures of housing affordability, accepting that what households can afford to pay for housing is related to their ability to cover other costs, and so not directly proportional to income. It proposes a new approach to defining and measuring housing affordability, based on the Minimum Income Standard (MIS). The paper then uses data from the Family Resources Survey (2008/09 to 2015/16) to examine housing affordability within the rented sector across the UK, exploring the value of this measure both in revealing the scale of the 'problem' and assessing the likely impact of suggested interventions.